The autism symptom interview, school‐age: A brief telephone interview to identify autism spectrum disorders in 5‐to‐12‐year‐old children. Issue 1 (10th June 2016) - Bishop, Somer L.; Huerta, Marisela; Gotham, Katherine; Alexandra Havdahl, Karoline; Pickles, Andrew; Duncan, Amie; Hus Bal, Vanessa; Croen, Lisa; Lord, Catherine
Abstract : This study reports on the initial validation of the Autism Symptom Interview (ASI), School‐Age, a brief (15–20 min) phone interview derived from questions from the Autism Diagnostic Interview‐Revised (ADI‐R). The ASI, School‐Age was administered by interviewers with minimal training to parents of children ages 5 to 12 who had all been previously identified with (or referred for assessment of) ASD or another neurodevelopmental disorder. Children then underwent a comprehensive assessment to determine a best‐estimate clinical diagnosis of ASD ( n  = 159) or non‐ASD (e.g. language disorder, intellectual disability, ADHD; n  = 130). Clinicians who conducted the assessments were blind to ASI results. ROC analyses compared ASI scores to clinical diagnosis. Due to the small number of participants with non‐ASD diagnoses who were classified as nonverbal (i.e. not yet using phrases on a daily basis), it was not possible to assess sensitivity and specificity of the nonverbal algorithm in this sample. The verbal algorithm yielded a sensitivity of 0.87 (95% CI = 0.81–0.92) and a specificity of 0.62 (95% CI = 0.53–0.70). When used in conjunction with the Autism Diagnostic Observation Schedule (ADOS), sensitivity and specificity were 0.82 (95% CI = 0.74–0.88) and 0.92 (95% CI = 0.86–0.96), respectively. Internal consistency and test‐retest reliability were both excellent. Particularly for verbal school age children, the ASI may serve as a useful tool to more quickly ascertain or classify children with ASD for research or clinical triaging purposes. Additional data collection is underway to determine the utility of the ASI in children who are younger and/or nonverbal. Autism Res 2017, 10: 78–88 . © 2016 International Society for Autism Research, Wiley Periodicals, Inc.